Proclaiming the Qur'an and its Translation in Mosques: Phenomenological and Ethnomethodological Approaches - Yahya, Muhammad; Komarudin, Edi (UIN Sunan Gunung Djati Bandung, 2024)
The recitation of the Qur'an has become a ubiquitous practice in mosques and Islamic boarding schools, fostering a profound acculturation between Arab culture and local culture. This phenomenon is particularly evident in institutions such as the Ponpes Ulul Albab Mosque, where the ritualistic recitation of the Qur'an serves as a cornerstone of religious and cultural identity. This research employs a phenomenological and ethnomethodological approach to evaluate the effectiveness and societal responses to this activity. By examining the lived experiences and social interactions surrounding Qur'anic recitation, this study aims to elucidate the complex dynamics involved in the cultural transmission of Islamic practices. The findings of this research indicate a positive acceptance from the community, with significant affective, cognitive, and conative impacts. The affective dimension reveals a profound emotional resonance among participants, as the recitation of the Qur'an evokes feelings of spiritual connection and communal solidarity. The cognitive dimension highlights the intellectual engagement and understanding that arises from the meticulous study and recitation of the sacred text. Furthermore, the conative dimension underscores the motivational and behavioral changes observed among participants, as they strive to perfect their recitation skills and integrate these practices into their daily lives. This study contributes significantly to the understanding of modern religious practices and cultural interactions in the context of Qur'anic recitation in mosques.